Host genetics impact on SARS-CoV-2 vaccine-induced immunoglobulin levels and dynamics: The role of TP53, ABO, APOE, ACE2, HLA-A, and CRP genes - Gemmati, Donato; Longo, Giovanna; Gallo, Ines; Silva, Juliana Araujo; Secchiero, Paola; Zauli, Giorgio; Hanau, Stefania; Passaro, Angelina; Pellegatti, Patrizia; Pizzicotti, Stefano; Serino, Maria Luisa; Singh, Ajay Vikram; et al. (Frontiers in Genetics, 2022)
Background. Development and worldwide availability of safe and effective vaccines against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) to fight severe symptoms of coronavirus disease 2019 (COVID-19) and block pandemic have been a great achievement and stimulated researchers on understanding the efficacy and duration of the different vaccine types. Methods. We investigated the levels of anti-SARS-CoV-2 antibodies (IgG) and neutralizing antibodies (NAbs), in 195 healthy adult subjects belonging to the staff of the University/Hospital of Ferrara (Italy) starting from 15 days up to 190 days (about 6 months) after the second dose of the BNT162b2 (Pfizer–BioNTech) mRNA-based vaccine (n=128) or ChAdOx1 (AstraZeneca) Adenovirus-based vaccine (n=67) using a combined approach of serological and genomics investigations. Results. A strong correlation between IgG and NAbs levels was detected during the 190 days of follow-up (r2=0.807; P<0.0001), confirmed during the first 90 days (T1) after vaccination (r2=0.789; P=0.0001), during the 91-190 days (T2) after vaccination (r2=0.764; P=0.0001) for both vaccine types (r2=0.842; P=0.0001 and r2=0.780; P=0.0001 for mRNA- and Adenovirus-based vaccine respectively). Besides age (P<0.01), sex (P=0.03) and type of vaccine (P<0.0001), which partially accounted for the remarkable individual differences observed in the antibody levels and dynamics, interesting genetic determinants appeared as significant modifiers of both IgG and NAbs response among the selected genes investigated (TP53, rs1042522; APOE, rs7412/rs429358; ABO, rs657152; ACE2, rs2285666; HLA-A rs2571381/rs2499; CRP, rs2808635/rs876538; LZTFL1, rs35044562; OAS3, rs10735079; SLC6A20, rs11385942; CFH, rs1061170; ACE1, ins/del, rs4646994). In detail, regression analysis and mean antibody levels comparison yielded appreciable differences after genotype stratification (P1 and P2 respectively for IgG and NAbs distribution) in the whole cohort and/or in the mRNA-based vaccine in the following genes: TP53, rs1042522 (P1=0.03; P2=0.04); ABO, rs657152 (P1=0.01; P2=0.03); APOE, rs7412/rs429358 (P1=0.0018; P2=0.0002); ACE2, rs2285666 (P1=0.014; P2=0.009); HLA-A, rs2571381/rs2499 (P1=0.02; P2=0.03); CRP, rs2808635/rs876538 (P1=0.01 and P2=0.09). Conclusions. High- or low-responsive subjects can be identified among healthy adult vaccinated subjects after targeted genetic screening. This suggests that favorable genetic backgrounds may support the progression of an effective vaccine induced immune response, though no definite conclusions can be drawn on the real effectiveness ascribed to a specific vaccine .............